2001
DOI: 10.1007/pl00011530
|View full text |Cite
|
Sign up to set email alerts
|

Troubleshooting in Mechanics: A Heuristic Matching Process

Abstract: International audienceThis paper deals with expert operators' reasoning processes in troubleshooting. We want to know more about the information that experienced operators use. In a previous study we studied electronics troubleshooting. We found that experts used surface cues in order to implement heuristic rules even if the latter are not relevant to the current fault. We now wish to study the field of mechanics. An experiment was conducted in order to test the hypothesis of a heuristic rule-based level of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Updating a mental model is a crucial step in this kind of diagnosis-like activity and it can be flawed even among expert operators. This has been experimentally demonstrated among mechanics and electronics operators (Besnard, 2000;Besnard & Cacitti, 2001) and has been the cause of other air crashes (NTSB, 1997;METT, 1993). So it is fair to say that the pilots of the DC-10 achieved a high level of performance.…”
Section: Desirable Violations: the Sioux City Emergency Landingmentioning
confidence: 83%
“…Updating a mental model is a crucial step in this kind of diagnosis-like activity and it can be flawed even among expert operators. This has been experimentally demonstrated among mechanics and electronics operators (Besnard, 2000;Besnard & Cacitti, 2001) and has been the cause of other air crashes (NTSB, 1997;METT, 1993). So it is fair to say that the pilots of the DC-10 achieved a high level of performance.…”
Section: Desirable Violations: the Sioux City Emergency Landingmentioning
confidence: 83%
“…Consequently, the difficulty to avoid the sudden pedestrian appearance was probably enhanced for experienced drivers who drove with a routine automation in a monotonous environment without being flexible. Indeed, routine automation might have produced difficulties to switch from an automatic action to a controlled one which can involve errors (Besnard, & Cacitti, 2001). …”
Section: Discussionmentioning
confidence: 99%
“…The five unsuccessful expert participants in the study demonstrated routine expertise, because they were unable to modify their automated procedures. However, the five remaining experts demonstrated adaptive expertise; their automated skills ultimately did not prohibit successful outcomes (Besnard & Cacitti, 2001).…”
Section: Adaptivity and Expertisementioning
confidence: 99%